Influence of age and sex on children’s ability to incorporate oral health habits after educational activities in schools - Martins, Tauane Ramaldes; Novo, Neil Ferreira; Ribeiro, Ana Paula; Ribeiro, Christiane Carvalho Fonseca; Juliano, Yara (Journal of Health Care, 2021)
The promotion of oral health is one of the pillars of preventive strategies in the emergence of dental changes in schoolchildren, as it is easier to incorporate health and hygienic habits in schools. However, to date, little is understood about the influence of age and sex on children’s ability to understand, improve, and adhere to oral health habits after educational actions in schools. Objective: To verify the influence of different age groups and sex on children’s ability to incorporate oral health habits after educational activities in schools. Materials and Methods: 173 children from a public State school, located in the South Region of the Capela do Socorro sub-prefecture of the city of São Paulo were evaluated and divided according to age into three groups: 6-7 years (n = 62), 8-9 years (n = 47), and 10-11 years (n = 27). Questionnaires were applied comprising the following topics: demographic and socioeconomic data, eating habits and oral hygiene, as well as the Simplified Oral Hygiene Index (SOHI). The educational strategy was performed with lectures, theater, and stories about brushing and oral hygiene. After two and four weeks of the educational action all data were reevaluated. Results: There was a significant difference between the 6 to 7 year age group compared to the 8 to 9 year and 10 to 11 year groups, with the youngest being more responsive and effective in oral health and hygiene, after two and four weeks of educational action at school. Regarding sex, there were no differences within and between groups. Conclusion: Schoolchildren of different age groups: 6 to 7, 8 to 9, and 10 to 11 years, showed effective improvements in oral health after two and four weeks of an educational action at school, regardless of sex. The incorporation of oral health habits was better in the 6 to 7 year age group.